Society Offers Half-Year Memberships at 50 Percent Off. (Computer (00189162), 2008)
This article discusses the promotional availability of half-year memberships in the Institute of Electrical & Electronic Engineers (IEEE) Computer Society. The limitations of half year IEEE Computer Society memberships in terms of subscriptions to this magazine are noted. The perks associated with membership in the IEEE Computer Society including access to their Digital Library are described.